2018
DOI: 10.2903/j.efsa.2018.5276
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of l‐arginine produced by fermentation with Escherichia coli NITE BP‐02186 for all animal species

Abstract: L-Arginine is considered as a non-essential amino acid for most adult mammalian species, but it is classified as essential for birds, fish, possibly reptiles and also for strict carnivores. L-Arginine produced by fermentation with Escherichia coli NITE BP-02186, genetically modified to enhance the production of L-arginine, is intended to be used in feed and water for drinking for all animal species and categories. The product under assessment does not give rise to any safety concern with regard to the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this way, Huang et al [30] performed a culture with two Gram-positive (S. aureus and L. monocytogenes) and two Gram-negative (E. coli and S. enteritidis) bacteria, which were incubated in a nutrient agar medium with a filter paper soaked with each of the thirteen NADESs they tested to extract rutin from tartary buckwheat hull. It was shown that none of the NADESs led to a decrease in the growth of bacteria with the exception of glycerol:L-arginine NADES, because, despite the fact that the individual components are nontoxic and were approved by the European Food Safety Authority [81,82], there occurs a charge delocalization as a result of a hydrogen bond, which makes the eutectic mixture toxic [83].…”
Section: Lycium Ruthenicummentioning
confidence: 99%
“…In this way, Huang et al [30] performed a culture with two Gram-positive (S. aureus and L. monocytogenes) and two Gram-negative (E. coli and S. enteritidis) bacteria, which were incubated in a nutrient agar medium with a filter paper soaked with each of the thirteen NADESs they tested to extract rutin from tartary buckwheat hull. It was shown that none of the NADESs led to a decrease in the growth of bacteria with the exception of glycerol:L-arginine NADES, because, despite the fact that the individual components are nontoxic and were approved by the European Food Safety Authority [81,82], there occurs a charge delocalization as a result of a hydrogen bond, which makes the eutectic mixture toxic [83].…”
Section: Lycium Ruthenicummentioning
confidence: 99%
“…The EFSA Scientific Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued three opinions on the safety and efficacy of L-arginine produced by genetically modified strains of C. glutamicum for all animal species (EFSA, 2007a;EFSA FEEDAP Panel, 2016, 2017a and an opinion on the safety and efficacy of L-arginine produced by fermentation with Escherichia coli NITE BP-02186 for all animal species (EFSA FEEDAP Panel, 2018c). The FEEDAP Panel issued one opinion on the safety and efficacy of the use of amino acids (chemical group 34) when used as flavourings for all animal species (EFSA FEEDAP Panel, 2014).…”
Section: 2mentioning
confidence: 99%
“…Application of phytochemicals that can affect fish health, growth and feed utilization is also spreading as extensive use of antibiotics has encouraged the evolution of resistant bacteria (Chakraborty and Hancz, 2011;Chakraborty et al, 2013). Encarnação (2016) gives an up-to-date summary of feed additives and introduces a new category of feeds called functional feeds for compound aquaculture feeds made with additives for ameliorating the animals' performance and improving intestinal health, stress, and disease resistance.…”
Section: Introductionmentioning
confidence: 99%